Can scenario planning catalyse transformational change? Evaluating a climate change policy case study in Mali. (February 2018) - Totin, Edmond; Butler, James R.; Sidibé, Amadou; Partey, Samuel; Thornton, Philip K.; Tabo, Ramadjita
Highlights: Scenario planning has the potential to enable networking and learning across boundary. Scenario process alone may not be sufficient to stimulate transformational change. For institutional and policy transformation to occur, a more extended learning process is required. Stakeholders engagement across scales is key for the scenario exercise to catalyse transformation. Abstract: The potential of participatory scenario processes to catalyse individual and collective transformation and policy change is emphasised in several theoretical reflections. Participatory scenario processes are believed to enhance participants' systems understanding, learning, networking and subsequent changes in practices. However, limited empirical evidence is available to prove these assumptions. This study aimed to contribute to this knowledge gap. It evaluates whether these outcomes had resulted from the scenario planning exercise and the extent to which they can contribute to transformational processes. The research focused on a district level case study in rural Mali which examined food security and necessary policy changes in the context of climate change. The analyses of interviews with 26 participants carried out 12 months after the workshop suggested positive changes in learning and networking, but only limited influence on systems understanding. There was limited change in practice, but the reported changes occurred at the individual level, and no policy outcomes were evident. However, by building the adaptive capacity of participants, the scenario process had laid the foundation for ongoing collective action, and potential institutional and policy transformation. We conclude that to enhance the resilience of agricultural and food systems under climate change, participatory scenario processes require a broader range of cross-scale actors' engagement to support transformational changes. Such process will both catalyse deeper learning and more effective link with national level policy-making process. In addition, individual scenario planning exercises are unlikely to generate sufficient learning and reflection, and instead they should form one component of more extensive and deliberate stakeholder engagement, learning and evaluation processes.